KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN KEGIATAN EKSTRAKURIKULER PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH ATAS NEGERI 3 TANJUNG JABUNG TIMUR - Aini, Nur Sarifa; Salim, Agus; Madyan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the leadership of the school principal in developing Islamic Religious Education extracurricular activities at State Senior High School 3 Tanjung Jabung Timur. The background of this research is based on the importance of extracurricular religious activities as a medium for developing students’ talents, interests, religious awareness, and character formation, which cannot be optimally achieved through intracurricular learning alone. The success of these activities is strongly influenced by the leadership role of the principal in planning, organizing, implementing, and supervising school programs. This research employed a qualitative approach with a descriptive case study design. Data were collected through observations, in-depth interviews, and documentation involving the principal, teachers, extracurricular supervisors, and students. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the principal plays a significant role as an educator, manager, and motivator in facilitating the development of Islamic Religious Education extracurricular activities, particularly in Qur’anic recitation and Islamic arts programs. Supporting factors include institutional support, teacher commitment, and student enthusiasm, while inhibiting factors involve limited facilities, time constraints, and variations in students’ religious competencies. The development of these extracurricular activities has a positive impact on students’ religious character, discipline, self-confidence, and understanding of Islamic values. The study concludes that effective and visionary school leadership is essential for the successful development of Islamic Religious Education extracurricular activities. Strengthening leadership management and improving supporting resources are recommended to enhance the sustainability and quality of these programs.